2021
DOI: 10.3390/md19030166
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Activated with Genipin: A Nontoxic Natural Carrier for Tannase Immobilization and Its Application in Enhancing Biological Activities of Tea Extract

Abstract: In this work, a non-toxic chitosan-based carrier was constructed via genipin activation and applied for the immobilization of tannase. The immobilization carriers and immobilized tannase were characterized using Fourier transform infrared spectroscopy and thermogravimetric analysis. Activation conditions (genipin concentration, activation temperature, activation pH and activation time) and immobilizations conditions (enzyme amount, immobilization time, immobilization temperature, immobilization pH, and shaking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 83 publications
(99 reference statements)
0
2
0
1
Order By: Relevance
“…It is shown that tannase treatment increases the polyphenols recovery rate in the extraction process due to the hydrolysis of ferulic acid dimers in the plant cell wall (Shao et al., 2020). In addition, the biological activities of tannase‐treated tea extracts, such as antioxidant activity and inhibitory effect on digestive enzymes (α‐amylase), also increase (Wang, Chen, et al., 2021). Increasing the content of GA by tannase‐treated green tea extract improves the free radical scavenging activity (Baik et al., 2015).…”
Section: Value‐added Utilization Of Pruned Tea Biomass In the Food In...mentioning
confidence: 99%
“…It is shown that tannase treatment increases the polyphenols recovery rate in the extraction process due to the hydrolysis of ferulic acid dimers in the plant cell wall (Shao et al., 2020). In addition, the biological activities of tannase‐treated tea extracts, such as antioxidant activity and inhibitory effect on digestive enzymes (α‐amylase), also increase (Wang, Chen, et al., 2021). Increasing the content of GA by tannase‐treated green tea extract improves the free radical scavenging activity (Baik et al., 2015).…”
Section: Value‐added Utilization Of Pruned Tea Biomass In the Food In...mentioning
confidence: 99%
“…The α-glucosidase had a more substantial inhibitory effect than αamylase [46]. The apparent variation in the inhibition effect of α-amylase and α-glucosidase might lead to undigested sugars reaching the colon, resulting in intestinal microbial digestion and successive intestinal illnesses, including abdominal discomfort, constipation, and diarrhea [47]. The bioactive compounds coated over the surface of MAL-CNPs are thought to be promising and efficient inhibitors of α-amylase as well as α-glucosidase.…”
Section: α-Amylase Inhibitory and α-Glucosidase Inhibitory Assaysmentioning
confidence: 99%
“…Despite the previously mentioned benefits, the enzyme-catalyzed transformation of tannin using tannase still faces several key challenges. For example, the complicated purification process, high production cost, insufficient enzyme stability, limited enzyme selectivity or specificity, low tolerance in the presence of inhibitors, finite application conditions, and inability to recycle after every use of free forms make this approach unsustainable for the long-term usage in industrial applications. , In this situation, immobilization of enzymes on a solid support is regarded as an effective strategy to overcome the above-mentioned limitations. Stable supports for tannase immobilization include calcium alginate beads, chitosan, manganese nanoparticles, magnetic nanoparticles, multiwalled carbon nanotubes, and silica oxide nanoparticles . The immobilization yield and reusability have been improved to a certain extent, but some major drawbacks remain.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 In this situation, immobilization of enzymes on a solid support is regarded as an effective strategy to overcome the above-mentioned limitations. 20−22 Stable supports for tannase immobilization include calcium alginate beads, 23−25 chitosan, 26 manganese nanoparticles, 27 magnetic nanoparticles, 28 multiwalled carbon nanotubes, 29 and silica oxide nanoparticles. 30 The immobilization yield and reusability have been improved to a certain extent, but some major drawbacks remain.…”
Section: ■ Introductionmentioning
confidence: 99%